Patterns in CSCW Modeling - Paludo, Marco; Burnett, Robert; Jamhour, Edgard (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1998)
Modeling object-oriented systems is usually presented in a great variety of methods, however few of them consider patterns and reuse issues in its structure. The purpose of this article is to present some CSCW characteristics and put them into two different approaches of system modeling. One pure object-oriented and other pattern-oriented. The focus is to stress the particularities of groupware applications, nevertheless traditional ones can also be addressed. Some object-oriented modeling characteristics are presented initially, establishing comparisons of Peter Coad's pattern-oriented methodology with others, followed by the modeling of a Project Management case study system wilh both approaches. The results are presented by comparing both modeling considering the static, dynamic and functional modeling, follow by the conclusions of the work.